Experimental Pulp-Capping Agent Radiopaque Dicalcium Silicate Cement Facilitates Dentinogenesis - Kuo, Wei-Ting; Li, Xin; Chen, Fang-Yuan; Wang, Yan-Jie; Chen, Zhi; Ding, Shinn-Jyh; Zhang, Lu (Frontiers in Materials, 2021)
This study was designed to comparatively evaluate an experimental pulp-capping agent radiopaque dicalcium silicate cement (RDSC), white-colored mineral trioxide aggregate (WMTA), iRoot BP Plus and Biodentine both ex vivo and in vivo. Fourier Transform infrared spectroscopy (FTIR) and X-ray diffraction (XRD) were utilized to analyze the phase composition of pulp-capping agents. The surface morphology and element analysis were finished by Scanning electron microscopy (SEM) and Energy Dispersive X-Ray Spectroscopy (EDX). Color stability of the cements and pulp responses induced by different cements were examined by ex-vivo human tooth culture model and in-vivo miniature pig model. Micro-computed tomography was used for quantitative evaluation of the newly formed mineralized tissue. RDSC exhibited discoloration in both models, while WMTA exhibited more visible discoloration. The occurrence of discoloration for WMTA was significantly higher than that of RDSC (p < 0.05), iRoot BP Plus and Biodentine on the 7th day, also higher (p < 0.05) than that of iRoot BP Plus and Biodentine on the 70th day. Mineralized foci were noted in all 7-day groups except the control group both ex vivo and in vivo. Intact and complete reparative dentin bridge formation which possessed tubular structures was noted in all 70-day groups in vivo. RDSC appeared to induce the thickest dentin bridge formation among all these pulp-capping agents which showed statistically significant difference to that of Biodentine (p < 0.05). With decent biological properties, RDSC may have the potential to be a pulp-capping agent recommended in the non-aesthetic area alternative to WMTA, Biodentine and iRoot BP Plus.